Follicular thyroid tumours: a study of laminin and type IV collagen in basement membrane and endothelium. Issue 10 (October 1985) - Kendall, C H; Sanderson, P R; Cope, J; Talbot, I C
Abstract : Immunocytochemical stains for laminin and type IV collagen can be used as markers for basement membrane and vascular endothelium. Thirty four follicular thyroid lesions were examined using these techniques to investigate two aspects: firstly, the relation between the extent of invasion and the integrity of basement membrane; secondly, whether the techniques could enhance the detection of tumour vascular invasion. The results showed that although basement membrane was lost in widely invasive tumours, preservation was seen in most but not all encapsulated tumours. The potential for improved recognition of vascular invasion was also found.